Distance education in Kingdom of Saudi Arabia and United Kingdom: A comparative study - Alkhiri, Mohammed Noah; Alkhiri, Talal Aqeel (Journal of Educational and Psychological Sciences, 2021)
This paper aims to shed light on distance education in the United Kingdom and comparing it to distance education in the Kingdom of Saudi Arabia, the extent of its use in improving the processes of distance learning and education, and ways to overcome the problems facing distance education in the Kingdom of Saudi Arabia.The study relied on reports and analysis of international data conducted by the Organization for Economic Cooperation and Development (OECD).Among the most important findings of the study: It is possible to benefit from the experience of the United Kingdom in distance learning, and there are significant differences in distance learning between the two countries, and there are few similarities.Among the most important recommendations of the study: To benefit from the experiences of British universities and institutions in distance education, and to simulate the platforms and applications used in distance education in the United Kingdom and how to benefit from them, and to benefit from the experience of the United Kingdom in responding to economic growth and bridging the digital divide by using the Internet in schools to teach academic subjects.
Keywords: Distance education; United Kingdom; Saudi Arabia; Improving distance education